(3GdWad GdYQHj h KbGaI GdeLJeY (B:s (3YjfGJ ef bUU GdCWaGd (B/s - (3GdMQ, PcGAs ((3dHfGf (B:s (3OGQ GdMOGKI ,s, 1984)
(3cj jbhe COH GdCWaGd Ydi CSS SdjeI h cj fLjH Ydi cGaI GMJjGLGJ GdWad dG HO ef Gf jchf GdYed eFSSG LeGYjG h dG HO ef JVGaQ LghO YdeGA GdfaS h GdJQHjI h YdeGA GddZI h GdGOHGA h GdQSGejf h GdHGMKjf HcGaI ddHOA HGdNWs
Keywords: (3GdJQHjIs; (3GdKbGaIs; (3GdWads; (3GdeLJeYs